Development of Indonesian Gait database using 2D optical motion analyzer system. - Mahyuddin, Andi Isra
In the present work, a previously developed optical motion-capture system combined with software for 2D clinical gait analysis is utilized to obtain gait data of Indonesian subjects. The system consists of a video camera with a maximum speed of 90 fps, LED markers, PC and technical computing software, which are developed for tracking markers attached to human body during motion and to calculate kinematics and kinematics parameters of human gait. This work presents only the kinematics gait parameters of 212 participating subjects obtained by the developed optical 2D motion analyzer system and software. Prior to measurement, the body posture of each subject is evaluated to ensure normalcy. The subject is instructed to walk in a specially-arranged measurement area. The spatiotemporal gait parameters such as stride-length, cadence, cycle-time, and speed as well as joint angles, are evaluated. The gait data of the 212 participating subjects that has been collected are compared to data available in literature. Based upon favorable comparisons, the data presented in this work could serve as the basis for the establishment of Indonesian normal gait database. Future works involving more participating subjects and comparative analysis to abnormal gait is deemed necessary and should be useful to assist physicians in diagnosing, and planning the rehabilitation program for the patients.
Keywords: Gait Analysis; Gait parameters; Motion analyzer system; Gait database